War in Worcester: : Youth and the Apartheid State - Weber, Samuel, 1940- (Book collections on Project MUSE., 2004)
Ever since Aristotle's Poetics, both the theory and the practice of theater have been governed by the assumption that it is a form of representation dominated by what Aristotle calls the "mythos," or the "plot." This conception of theater has subordinated characteristics related to the theatrical medium, such as the process and place of staging, to the demands of a unified narrative. This readable, thought-provoking, and multidisciplinary study explores theatrical writings that question this aesthetical-generic conception and seek instead to work with the medium of theatric.